Warriors : Cats of the Clans - Hunter, Erin; Illustrated by McLoughlin, Wayne (New York HarperCollins, 2008)
Rock, the keeper of the world beneath the world, tells about the most famous cats of the warriors Clans as well as the rogues, kittypets, and others, to three kits that have recently entered his realm.
Include Color Illustrations
Keywords: Children's stories